Grievances and Third-Party Intervention / Les tiers et le règlement des griefs - Chartier, Roger (Relations industrielles / Industrial Relations, 1960)
Summary Grievance is but one form of industrial conflict. It must be seen in the light or the global industrial relations situation of the parties. Its functions are many, whether it be a conflict over rights or over interest. The main thing is that the parties keep the closest possible control over the produce by resort to private arbitration.